SpectraPlot.com: Integrated spectroscopic modeling of atomic and molecular gases. (October 2017) - Goldenstein, Christopher S.; Miller, Victor A.; Mitchell Spearrin, R.; Strand, Christopher L.
Highlights: Description of SpectraPlot architecture, simulation tools, and user interface. Full description of the absorption and emission spectroscopy models employed by SpectraPlot. Introduction and evaluation of a far-wing cutoff criterion for decreasing computational time of absorption and emission spectra. Abstract: SpectraPlot is a web-based application for simulating spectra of atomic and molecular gases. At the time this manuscript was written, SpectraPlot consisted of four primary tools for calculating: (1) atomic and molecular absorption spectra, (2) atomic and molecular emission spectra, (3) transition linestrengths, and (4) blackbody emission spectra. These tools currently employ the NIST ASD, HITRAN2012, and HITEMP2010 databases to perform line-by-line simulations of spectra. SpectraPlot employs a modular, integrated architecture, enabling multiple simulations across multiple databases and/or thermodynamic conditions to be visualized in an interactive plot window. The primary objective of this paper is to describe the architecture and spectroscopic models employed by SpectraPlot in order to provide its users with the knowledge required to understand the capabilities and limitations of simulations performed using SpectraPlot. Further, this manuscript discusses the accuracy of several underlying approximations used to decrease computational time, in particular, the use of far-wing cutoff criteria.